Analysis of Road Carriers Liability for Robbery of Cargo According to CMR Convention - Šker, Tristan (Promet - Traffic&Transportation, 2003)
Road carrers are increasingly facing the risk of theft androbbery of cargo which they are carrying. CMR Convention allowsthe earners to be exonerated from their liability in the caseof circumstances which the ca'ier could not avoid and theconsequences of which he was unable to prevent. Unfortunately,there is no common inte1pretation and application inpractice at the European courts of this part of CMR Convention.With the analysis of court judgements in case of robbery ofthe road ca'ier in Italy it is possible to clarify the interpretationof such events and their connection with the exclusion of liabilityof the road earners contained in the CMR Convention.